Remarkably bright creatures : a novel - Van Pelt, Shelby; OverDrive, Inc. (New York, NY : Ecco, 2022)
"For fans of A Man Called Ove, a luminous debut novel about a widow's unlikely friendship with a giant Pacific octopus reluctantly residing at the local aquarium-and the truths she finally uncovers about her son's disappearance 30 years ago"--
Electronic audio file.
Electronic reproduction.
Keywords: Advantage title -- Fiction; Octopuses -- Fiction; Widows -- Fiction; Human-animal relationships -- Fiction; Mothers and sons -- Fiction; Animal fiction; Novels; Electronic audio books